Uranium–lead, extraterrestrial, planetary materials - Nemchin, Alexander (2015)
© Springer Science+Business Media Dordrecht 2015. Development of microanalytical methods of isotope analysis allowing in situ age determination in the small (few tens of micrometers) areas inside individual grains resulted in significant expansion of U–Pb age database of planetary materials, which include lunar and Martian samples. Combined with detailed imaging of the samples, these ages give unprecedented new information about the origin and evolution of the planets and have direct and indirect influence on the development of ideas and models for evolution of our own planet Earth. A variety of planetary materials of diverse composition and origin can be dated using U–Pb system, as U is concentrated in the quantities sufficient for analysis in a number of different minerals and glasses. Some of these materials, such as zircon in lunar breccias, have been extensively studied during the last decade, while capability of others remain mostly unexplored leaving a significant potential for the future research and new discoveries.